RI 2386 Commuted Smokeless Powder as Blasting Agent - C. E. Munroe (The National Institute for Occupational Safety and Health (NIOSH), 1922)
In order to meet the emergencies of the world w􀌲r, tne quantities of explosivea produced in the Unitecl States, and the number of explosives plants were 􀀨onti:.1.1.:l,lly 􀀱ncreased so that when the armistice was declared the Government had on hand larg􀎆 􀎇..mounts oi militazy explosives in excess of existing military needs. Tl􀎷e stor3.gs of these explosives entailed a liirge expense and their protection ne􀏳essitatei the employment of m'3.l'lY men who could be better employed otherwise in the military est􀁼lish.11ent. Moreover, mar.y ex.plo􀂗ives, like QJ.l other material, deteriorate on prolonged storage, They lose th􀑔t precise definiteness of properties and behavior on which reliance· is placed in military operations, The continued expen3e and d3.nger 􀒯ttending storage of theae explosives might be diminished by dcst􀓢1et1on of the surplus beyond immediate needs, but such·deetniction is danger• ou5 qnd coetly. Hence, the evident solution o! the problem was the salvage 􀃆d prompt ut111zation of the ru.rplua •